Synthetic Methods and Pharmacological Potentials of Isothiocyanate Derivatives - Khidre, Rizk E.; Borik, Rita M.; Behalo, Mohamed S.; Elkarim, Iman A. Gad; Esam, Ahmed (Mini-Reviews in Organic Chemistry, 2025)
The present review deals with different synthetic methods of isothiocyanates, including alcohols, aryl chlorides, primary amines, carboxylic acid or carboxylic acid derivatives, cleavage of heterocyclic compounds, and alkene derivatives as a starting material. Furthermore, the thermal rearrangement of thiocyanate, decomposition of thiourea derivatives, and natural isothiocyanates are discussed. It also includes the chemical reaction of isothiocyanates derivatives, such as reaction with alkenes and aromatic compounds, addition of water and amine derivatives, reaction with amino alcohol derivatives, reaction with amino acids and their derivatives, reaction with hydrazine and acid hydrazide derivatives, and miscellaneous reactions. In addition, this review summarizes different pharmaceutical applications of isothiocyanate derivatives, such as anticancer, antimicrobial, antioxidant, and anti-inflammatory activities.
Keywords: pharmaceutical applications